The Dynamic wheel-Rail Contact Stresses for Wagons on Various Tracks - Xia, F.; Cole, C.; Wolfs, Peter (Institute of Materials Engineering Australia, 2006)
The maximal stress and tangential surface forces at the wheel rail contact elliptic area are affected by the wheel rail contact dynamic load and creepages. Dynamic wheel load is related to the wagon dynamic system, track and wheel rail interaction. Creepages are related to the motion of wheelset and wheel rail contact parameters. The paper presents an analysis of the effects of creepages on wheel rail contact forces. A complete Australia wagon with three-piece bogies was modelled and various tracks were selected for the simulation of dynamic wheel rail contact stresses. The results show that the maximal normal wheel rail contact stresses is under 1600Mpa in a range of conditions typical of normal operation.